Frequent amplification of a short chain dehydrogenase gene as part of circular and linear amplicons in methotrexate resistant Leishmania. - Papadopoulou, B (1993)
The H locus of Leishmania codes for a short chain dehydrogenase gene (ltdh) that is involved in antifolate resistance. Leishmania tarentolae cells, selected in a step by step fashion for resistance to the antifolate methotrexate (MTX), frequently amplified ltdh in response to drug selection. Both circular and linear extrachromosomal amplicons were generated de novo from the chromosomal H locus and several contained inverted duplications. At least four different rearrangement points were used during the formation of amplicons, with one of them used preferentially. All mutants highly resistant to MTX, whether or not they have the H locus amplified, showed a decreased steady-state accumulation of MTX. Nevertheless, two types of transport mutants were clearly discernable. In the first type, accumulation was reduced four to five-fold, whereas in the second class of mutants, accumulation was reduced more than 50-fold. The ltdh gene was amplified in all the mutants with the transport mutation of the first type, but not in all the mutants with a more pronounced decrease in the steady-state accumulation of MTX. Both types of transport mutation, leading to the reduction in MTX accumulation, arose early during the selection process and were stable even when cells were grown in absence of the drug for prolonged period.